Long-term Outcomes of Military Service in Aging and the Life Course: A Positive Re-envisioning. (9th December 2015) - Spiro, Avron; Settersten, Richard A.; Aldwin, Carolyn M.
Abstract: Most research on military service focuses on its short-term negative consequences, especially the mental and physical injuries of those deployed in warzones. However, studies of long-term outcomes reveal surprisingly positive effects of military service—both those early in adulthood that grow over time and others that can emerge later in life. These multidomain effects have been found in veterans of World War II and the Korean War and are now being seen in veterans of the Vietnam War. Although some are directly attributable to public policies such as the GI Bill, which facilitate educational and economic gains, there are personal developmental gains as well, including autonomy, emotional maturity and resilience, mastery, and leadership skills, that lead to better health and well-being in later life. These long-term effects vary across persons, change over time within persons, and often reflect processes of cumulative advantage and disadvantage. We propose a life-span model of the effects of military service that provides a perspective for probing both long-term positive and negative outcomes for aging veterans. We further explicate the model by focusing on both sociocultural dynamics and individual processes. We identify public-use data that can be examined to evaluate this model, and offer a set of questions that can be used to assess military service. Finally, we outline an agenda for dedicated inquiry into such effects and consider policy implications for the health and well-being of aging veterans in later life.